2010
DOI: 10.1183/09031936.00169509
|View full text |Cite
|
Sign up to set email alerts
|

Dermcidin identification from exhaled air for lung cancer diagnosis

Abstract: 9 Vine MF, Stein L, Weigle K. Gender differences in response to the multitest CMI skin test in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…It has been reported that antimicrobial peptides such as dermcidin, lysozyme, lactoferrin, psoriasin, cathelicidin and β‐defensins are present in human sweat and dermcidin‐derived peptides were identified as the principal antimicrobial components . Reduced presence of dermcidin‐derived peptides was detected in the sweat of atopic dermatitis patients in association with an impaired cutaneous antimicrobial defense, while its increased expression has been demonstrated in different cancer cells . Beside their antibiotic properties, some components of the skin's chemical barrier are also able to recruit inflammatory cells and induce cytokine release …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that antimicrobial peptides such as dermcidin, lysozyme, lactoferrin, psoriasin, cathelicidin and β‐defensins are present in human sweat and dermcidin‐derived peptides were identified as the principal antimicrobial components . Reduced presence of dermcidin‐derived peptides was detected in the sweat of atopic dermatitis patients in association with an impaired cutaneous antimicrobial defense, while its increased expression has been demonstrated in different cancer cells . Beside their antibiotic properties, some components of the skin's chemical barrier are also able to recruit inflammatory cells and induce cytokine release …”
Section: Introductionmentioning
confidence: 99%
“…7 Reduced presence of dermcidinderived peptides was detected in the sweat of atopic dermatitis patients in association with an impaired cutaneous antimicrobial defense, 7 while its increased expression has been demonstrated in different cancer cells. 10,11 Beside their antibiotic properties, some components of the skin's chemical barrier are also able to recruit inflammatory cells and induce cytokine release. 12 Little is known about the causes and consequences of qualitative and quantitative alterations of the human sweat proteins, moreover, the composition of the sweat itself has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that dermcidin serves a role in the carcinogenesis of a number of tumor types, including lung cancer (16,37), melanoma (17,38), breast cancer (39)(40)(41), hepatocellular carcinoma (HCC) (42,43), prostatic carcinoma (44) and pancreatic cancer (15). Dermcidin may also affect breast cancer development through the ERBB signaling pathway (41).…”
Section: Discussionmentioning
confidence: 99%
“…mounting studies have reported that dermcidin (15)(16)(17), GAPDH (18), annexin (19,20), calmodulin-like protein (21,22), cathepsin-D (23) and suprabasin (24) are associated with malignant tumors. Based on this, RNA-protein interaction prediction was used to assess whether these proteins were binding candidates for STCAT3.…”
Section: Screening and Identification Of Dermcidin As A Novel Bindingmentioning
confidence: 99%
“…Particularly, previous results on the localization of Y-P30 in rodents are erroneous, because the dermcidin gene has not been identified in rodents [12,17]. Given that the Y-P30/dermcidin precursor is present in skin, sweat [12] and tears [41] and probably breath [42,43] the likelihood of contamination is relatively high. Moreover, antibodies might cross-react with remotely related peptides in rodents.…”
Section: Discussionmentioning
confidence: 99%